The insula modulates arousal-induced reluctance to try novel tastes through adrenergic transmission in the rat - Rojas, Sebastián; Diaz-Galarce, Raúl; Jerez-Baraona, Juan Manuel; Quintana-Donoso, Daisy; Moraga-Amaro, Rodrigo; Stehberg, Jimmy (Frontiers in Behavioral Neuroscience, 2015)
Reluctance to try novel tastes (neophobia) can be exacerbated in arousing situations, such as when children are under social stress or in rodents, when the new taste is presented in a high arousal context (HA) compared to a low arousal context (LA). The present study aimed at determining whether adrenergic transmission at the Insula regulates the reluctance to try novel tastes induced by arousing contexts. To this end, a combination of systemic and intra-insular manipulations of adrenergic activity was performed before the novel taste (saccharin 0.1%) was presented either in LA or HA contexts in rats. Our results show that systemic adrenergic activity modulates reluctance to try novel tastes. Moreover, intra-insular microinjections of propranolol or norepinephrine were found to modulate the effects of arousing contexts on reluctance to try novel tastes. Finally, intra-insular propranolol blocked epinephrine-induced increased reluctance, while intra-insular norepinephrine blocked oral propranolol-induced decreases in reluctance and increased the reluctance to try novel tastes presented in low arousing contexts. In conclusion, our results suggest that the insula is a critical site for regulating the effects of arousal in the reluctance to try novel tastes via the adrenergic system.